Reprogramming DNA methylation in the mammalian life cycle: building and breaking epigenetic barriers - Seisenberger, Stefanie (The Royal Society, 2013)
In mammalian development, epigenetic modifications, including DNA methylation patterns, play a crucial role in defining cell fate but also represent epigenetic barriers that restrict developmental potential. At two points in the life cycle, DNA methylation marks are reprogrammed on a global scale, concomitant with restoration of developmental potency. DNA methylation patterns are subsequently re-established with the commitment towards a distinct cell fate. This reprogramming of DNA methylation takes place firstly on fertilization in the zygote, and secondly in primordial germ cells (PGCs), which are the direct progenitors of sperm or oocyte. In each reprogramming window, a unique set of mechanisms regulates DNA methylation erasure and re-establishment. Recent advances have uncovered roles for the TET3 hydroxylase and passive demethylation, together with base excision repair (BER) and the elongator complex, in methylation erasure from the zygote. Deamination by AID, BER and passive demethylation have been implicated in reprogramming in PGCs, but the process in its entirety is still poorly understood. In this review, we discuss the dynamics of DNA methylation reprogramming in PGCs and the zygote, the mechanisms involved and the biological significance of these events. Advances in our understanding of such natural epigenetic reprogramming are beginning to aid enhancement of experimental reprogramming in which the role of potential mechanisms can be investigated in vitro. Conversely, insights into in vitro reprogramming techniques may aid our understanding of epigenetic reprogramming in the germline and supply important clues in reprogramming for therapies in regenerative medicine.